The Effect of Customer Experience, Customer Satisfaction, and Perceived Security on Customer Loyalty at Gamerskin Aesthetic Clinic - Galang Saputro Wahyu Nugroho; Auditia Setiobudi (Majapahit Journal of Islamic Finance and Management, 2026)
The aesthetic service industry is experiencing rapid growth alongside increasing public awareness of health and beauty treatments. However, the high intensity of competition has made customer loyalty a crucial strategic issue. This study aims to analyze the influence of customer experience, customer satisfaction, and perceived security on customer loyalty at Gamerskin Aesthetic Clinic. This research employs a quantitative approach using a survey method. The research sample consists of 100 respondents who are active customers of Gamerskin Aesthetic Clinic, determined using a simple random sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that customer experience, customer satisfaction, and perceived security simultaneously have a significant effect on customer loyalty. Partially, customer experience and perceived security have the most dominant influence on customer loyalty. These findings confirm that customer loyalty in aesthetic clinics is determined not only by functional satisfaction but also by emotional experience and the medical safety assurance perceived by the customers.